Exploring Implications of Risk Communication Strategies in Diminishing Adversities of Misinformation and Disinformation Against Hepatitis Vaccination in Global South - Mehdi M; Raza SH; Yousaf M; Li B; Zaman U; Riaz S (Risk Management and Healthcare Policy)
Miqdad Mehdi,1 Syed Hassan Raza,2 Muhammad Yousaf,3 Bingqiang Li,1 Umer Zaman,4 Sohail Riaz5 1School of Law, Shanxi University, Taiyuan, 030006, People’s Republic of China; 2School of Media and Communication, Taylor’s University, Subang Jaya, Selangor, 47500, Malaysia; 3Centre for Media and Communication Studies, University of Gujrat, Gujrat, 50700, Pakistan; 4Endicott College of International Studies (ECIS), Woosong University, Daejeon, 34606, Korea; 5Media and Communication Studies, Comsat University Islamabad, Lahore Campus, Lahore, PakistanCorrespondence: Miqdad Mehdi; Bingqiang Li, School of Law, Shanxi University, Taiyuan, 030006, People’s Republic of China, Tel +86 15691753163, Email miqdadmehdi93@gmail.com; sdfxylbq@163.comBackground and Purpose: Concern over the low hepatitis immunization rates is growing. It is generally believed that misinformation and disinformation are the main barriers to the success of mass immunization campaigns. This study intends to investigate the matter of online misinformation and disinformation about hepatitis vaccination and its implications.Material and Methods: The researchers employed a cross-sectional research design vis-à-vis a web-based survey method to collect data. Data were collected from a nationally representative sample of 1931 internet users across Pakistan. Participation in the study was voluntary. Data collection continued for four months, from Mar 1, 2024, to Jun 30, 2024.Results: The “results” of structural equation modeling show that misinformation and disinformation substantially structure risk perception regarding hepatitis, which, in turn, impacts problem recognition, involvement recognition, and constraint recognition. Besides, the outcomes uncovered that the chain of problem identification impacts situational motivation, which drives risk communication behaviors. Also, these risk communication behaviors are closely linked to individuals’ motivation to receive the hepatitis vaccine.Conclusion: This research concludes that managing misinformation and disinformation via strategically designed, valid, and reliable digital interventions improves the public’s active response regarding willingness to get vaccinated against hepatitis. This study contributes to increasing public acceptance of the hepatitis vaccine by utilizing reliable and valid digital interventions to achieve a more active public health response.Keywords: misinformation, disinformation, global south, hepatitis, risk communication, vaccine